Implikasi Autopsi Forensik Dalam Penyidikan Tindak Pidana Pembunuhan - Sabono, Felia Naomi; Adam, Sherly; Lewerissa, Yanti Amelia (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Forensic autopsy is the examination of a corpse after death to determine the cause and manner of death, and to identify possible disease or injury to the body of a deceased person.Purposes of the Research: The purpose of this study is to analyze and discuss the implications of a forensic autopsy in the investigation of a crime of murder and the obstacles encountered in the forensic autopsy process.Methods of the Research: In this legal research, writing uses normative juridical research, problem approaches namely statutory approaches, conceptual approaches, and case approaches. The legal materials used are primary legal materials, secondary legal materials and tertiary legal materials.Results of the Research: The results of this study indicate that the implications of a forensic autopsy in the investigation of a crime of murder can find and obtain material truth, namely the truth that actually happened and there were errors and can be held criminally responsible for the perpetrators of a crime of murder in an investigation of a crime of murder in the process of proving and can convince the judge in deciding the case. The obstacles encountered in the forensic autopsy process in the crime of homicide were the refusal of an autopsy from the victim's family, the absence of forensic experts, the lack of facilities and infrastructure to support the implementation of a forensic autopsy.